PENGATURAN PERADILAN ADAT DALAM AWIG-AWIG DESA PAKRAMAN: STUDI PENDAHULUAN TENTANG EKSISTENSI PERADILAN ADAT DALAM KESATUAN MASYARAKAT HUKUM ADAT DESA PAKRAMAN - Sudantra, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 2 (2014), 2014)
This study aims to determine the regulation on customary justice in the traditional rules of awig-awig of  pakraman village, the rules made by the customary community unit of Pakraman village in Bali. This study focused on structure, competency, mechanism, and principle of customary justice. The result shows that structure and competency of customary justice have been regulated clearly on awig-awig of pakraman village, but the mechanism of customary justice doesn’t regulated clearly. Awig-awig of desa pakraman only regulates initial mechanism, namely the process of filing a case, but does not regulate mechanisms after the case was subsequently processed by the customary justice. It can be identified some principles in awig awig of pakraman village to be a guidance for the customary courts in resolving cases that occur on it’s jurisdiction
Keywords: awig-awig of pakraman village; customary justice; unity of customary law community